Gestión administrativa en la Microempresa “Workstech” reparación y mantenimiento de computadoras de la Parroquia La Unión del cantón Babahoyo, periodo enero -junio 2023. - Urrutia Maridueña, Wendy Jamileth (2023)
Organizational stability in the current environment represents a constant challenge. Only through the application of adequate administrative tools, a company can ensure its permanence in the market. Those companies that do not adapt to changes tend to disappear or lose their stability. The evolution in the internal structure of organizations has given rise to new trends in their strategic projection, which forces them to remain in a constant state of change and innovation. example of this dynamic is found in the province of Los Ríos, where economic activities are mainly focused on the commercialization of goods and services. This work is based on an exhaustive review of bibliographic sources and seeks to create an organizational design aimed at improving the administrative management of the microenterprise. The implementation of this design will allow the company to direct its resources effectively and efficiently. The methodology used facilitated the researcher's immersion in the microenterprise environment, which made it possible to identify their main needs and establish the guiding principles for the proposal and resolution of problems.